Adaptation Rate of Structural Requirements on the Iranian Medical Journals with the Criteria of Indexing Based on Scopus - Azam Shahbodaghi; Arezoo Farhadi; Maryam Shekofteh; Manoochehr Karami (Tehran University of Medical Sciences, 2017)
Background and Aim: In the recent years the number of science research health journals has increased in Iran. These journals should be based on the standards and criteria required in international indexing database. The aim of this study was to determine the adaptation rate of structural requirements on the Iranian medical journals with the criteria of indexing based on Scopus indexing database.      Materials and Methods: This study was a descriptive-applied study done using bibliometric methods. The statistical population was all of the science research journals in health ministry on 2014. The data collection tool was the inventory control extracted from Scopus database. The data was collected and analyzed by SPSS20 software and descriptive statistics methods. Results: The results showed that more than half of the biomedical journals were not based on the international editing statements and also, participation of the members of international editing committee was very low. The mean of international editing committee members was 83.3% and all of them were in Iran besides, participation of non Iranian authors was very low in these journals, with a participation rate of only 5.79%. Conclusion: The Iranian medical journals did not follow the expected criteria in Scopus indexing database in a satisfaction level. Adaptation to the expected criteria can facilitate the entering and indexing procedures for these health journals in Scopus indexing database.